Impact of air-sea exchange coefficients on the structure and intensity of tropical cyclones - Kwon, Young Cheol; Kim, Taekyun (TAO : Terrestrial, atmospheric, and oceanic sciences, 2017)
To examine the impact of air-sea exchange coefficients on the structure and intensity of tropical cyclones, sensitivity experiments are performed using the Weather Research and Forecasting (WRF) Model. A typhoon-like idealized vortex embedded in a calm environment is simulated using combinations of three different values of air-sea momentum and enthalpy exchange coefficients. In order to investigate the clear roles of each exchange coefficient, the experiments are designed that the two exchange coefficients change independently. For example, while the enthalpy exchange coefficient varies, the momentum exchange coefficient keeps its original value and vice versa. The track and intensity of sensitivity tests are analyzed to check the validity of the experiments. Results show that the track of the idealized vortices under a calm environment remains stationary, while the intensity varies with different air-sea exchange coefficients. The results indicate that changes in storm intensity with different enthalpy exchange coefficients are mainly related to an alteration in the amount of energy input to the storm, whereas the intensity changes with different momentum exchange coefficient values mostly result from angular momentum conservation due to changes in the size of the vortex. There is little change in the net energy input to the storms when the values of the momentum exchange coefficient are changed. Calculations of the volume-integrated angular momentum at the radius of the maximum winds confirm the different intensifying mechanisms found in this study.